Estudo taxonômico da família Characidae da drenagem do Rio Pindaré, Bacia do Rio Mearim, Maranhão, Nordeste do Brasil - GUIMARÃES, Erick Cristofore (2018)
One of the main challenges of modern Neotropical ichthyology consists to the systematics of Characidae, a family with approximately 1. 200 species valid, including about two thirds of all Characiformes diversity. Characidae is also the most widely distributed family of Characiformes, with representatives occurring from the south of the United States all to Argentinian Patagonia, and the center of Chile. However, most of this family’s diversity is concentrated from Panama to the Plata River system, and, more particularly, in the northern cis-Andean South American basins (Amazonian basin, Guyana rivers and Orinoco River basin). With the objective of carrying out a taxonomic study of Characidae species found at the Pindaré River drainage of the Mearim River basin, northeastern Brazil, we conducted 14 sampling campaigns during a period from 2012 to 2018. The Pindaré river is part of the coastal drainages of northeastern Brazil, and it is entirely included in the Amazonia Legal region of the Maranhão state. In our study, a total of 26,726 specimens belonging to Characidae were collected, comprehending 13 genera and 15 species. We present here 11 distribution expansions and describe new Characidae species, as well as new data on species taxonomy and distribution.